Variation in Amapasaurus tetradactylus (Reptilia: Squamata: Gymnophthalmidae), a rare Guiana lizard - Avila-Pires, Teresa Cristina Sauer de; Lima, Jucivaldo Dias; Hoogmoed, Marinus Steven; Lima, Janaína Reis Ferreira; Rocha, Wáldima Alves da (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2013)
The Guiana region is one of the better-preserved parts of Amazonia, but its fauna is still incompletely known. Amapasaurus tetradactylus was described in 1970, on the basis of two specimens from the upper Maracá river basin, Amapá, Brazil. Only between 2004-2006, during a series of expeditions in Amapá, new material of this species was obtained, and in 2008 it was collected also in northern Pará (at present it is also recorded from French Guiana). A total of 37 specimens, from six localities in Brazilian Guiana, is here examined, giving an idea of variation in scale characters and of its habitat. Present data makes it likely that the species is an endemic to the eastern part of the Guiana Shield, possibly in its central-southern portion.